2022
DOI: 10.3390/plants11141810
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Applying Different Doses of Selenite to Soil and Foliar at Different Growth Stage on Selenium Content and Yield of Different Oat Varieties

Abstract: (1) Background: With the increase in people’s consumption of processed oat products, the production of selenium (Se)-enriched oat has become a possibility to supplement the human body with Se. Therefore, the effects of various factors on the Se-enriched ability and yield of different oat varieties were comprehensively studied. (2) Methods: cv.“Pinyan 5” and cv.“Bayou 18” were applied at the stem-elongation stage and heading stage in the Jinzhong (JZ), and cv.“Bayou 1” and cv.“Jinyan 18” were applied at the hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The results indicated that millet treated with Se during the grain-filling period accumulated more Se in the grains [43]. Additionally, Hao et al reported that applying Se during the heading stage of oats led to increased Se accumulation in the grain portion as compared to the flowering stage [26]. Wang et al suggested that foliar Se application to wheat during the grain-filling stage, as opposed to the earlier growth stages or other stages, results in the highest grain Se content [62].…”
Section: Effect Of Crop Fertilization Site and Time On Se Accumulationmentioning
confidence: 95%
See 1 more Smart Citation
“…The results indicated that millet treated with Se during the grain-filling period accumulated more Se in the grains [43]. Additionally, Hao et al reported that applying Se during the heading stage of oats led to increased Se accumulation in the grain portion as compared to the flowering stage [26]. Wang et al suggested that foliar Se application to wheat during the grain-filling stage, as opposed to the earlier growth stages or other stages, results in the highest grain Se content [62].…”
Section: Effect Of Crop Fertilization Site and Time On Se Accumulationmentioning
confidence: 95%
“…The results indicated that, compared to selenate, selenite led to a greater accumulation of Se in grains. Hao et al reported that applying Se during the heading stage in oats resulted in a higher Se content in oat grains compared to the stem-elongation stage [26]. However, the results of Se biofortification in Finland also show that crop uptake of Se from soil-applied Se fertilizers is typically less than 10% [11].…”
Section: Introductionmentioning
confidence: 99%
“…Shengbao Cai et al investigated the activity changes in γ-aminobutyric acid (GABA), phytate and natural antioxidants during the fermentation of oat. GABA, total phenol content (TPC) and flavonoid content increased rapidly, while phytate, as an anti-nutritional component, decreased significantly in fermented oat during fermentation [ 28 , 81 ].…”
Section: Health Benefitsmentioning
confidence: 99%
“…Oat has been transformed from an unassuming feed crop to a leading player in the health and functional food ingredient industry, being hailed as the “third staple” [ 81 ] because of its nutritional value and therapeutic efficacy on a number of diseases including dyslipidemia, hypertension, vascular damage and diabetes [ 2 , 82 ]. The effects of oats on diabetes are attributed to the properties of maintaining the homeostasis of glucose and insulin levels as well as cholesterol-lowering properties.…”
Section: Health Benefitsmentioning
confidence: 99%
“…However, over 40 countries and ecological zones globally face severe Se deficiencies. Among these, 72% of the ecological zones of China are Se-deficient or exhibit low Se, leading to approximately 2/3 of the population of China experiencing varying degrees of Se deficiency [5]. Cereal crops serve as the primary source of dietary Se for humans.…”
Section: Introductionmentioning
confidence: 99%